Notes on the Morphology and Genesis of Mud Polygons on Mount Kenya, East Africa - Mahaney, William; Boyer, Michael (Géographie physique et Quaternaire, 1988)
ABSTRACTMud polygons forming in a valley train deposit in Teleki Valley on Mount Kenya were studied with respect to their physical, mineralogical, chemical and biological characteristics. Developing in fine-grained alluvium of postglacial age, those polygonal systems are composed of numerous, and nearly isomorphous units, that appear close to existing drainages in areas stripped of vegetation cover. Stream erosion and animal activity (particularly rodents and Mount Kenya hyrax, e.g. cony) appear to be primarily responsible for the loss of plant cover. Field tests show that periodic wetting and drying results in closure and reopening of polygonal cracks; freeze thaw activity was not observed to assist in developing polygonal ground shape. Subsequent laboratory tests on several samples confirm that the lack of expandable clay minerals might inhibit wetting-drying activity in individual polygon samples.